Design for acceptable risk in transportation pipelines. (1st January 2012) - Dawotola, Alex. W.; van Gelder, P.H.A.J.M.; Vrijling, J.K.
In this work, the probabilistic methods have been used to produce a methodology capable to estimate the acceptable level of risk in a cost-benefit framework. The benefits and the costs are weighed against associated risks to aid the decision making process on risk acceptance, from both the individual and societal perspective. Thereafter, acceptable individual and societal risk levels are defined based on historical trend of non-voluntary deaths and overall national fatalities. An example is used to explore the practical application of the method to critical infrastructures such as petroleum pipelines. The results show that the cost-benefit risk framework provides a safety standard that is acceptable from both individual and societal perspectives.